2016
DOI: 10.1093/nar/gkw776
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for single-stranded RNA recognition and cleavage by C3PO

Abstract: Translin and translin-associated factor-x are highly conserved in eukaroytes; they can form heteromeric complexes (known as C3POs) and participate in various nucleic acid metabolism pathways. In humans and Drosophila, C3POs cleave the fragmented siRNA passenger strands and facilitate the activation of RNA-induced silencing complex, the effector complex of RNA interference (RNAi). Here, we report three crystal structures of Nanoarchaeum equitans (Ne) C3PO. The apo-NeC3PO structure adopts an open form and unrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…In addition, negative-stained EM structure of full-length Drosophila C3PO at ∼15 Å resolution and cryo-EM structure of human-C3PO at ∼15 Å resolution were also reported ( 23 ). Notably, all the full-length C3POs adopt closed football-shaped structures, which are very similar to previous reported Translin homo-octamer structures ( 8 , 21 , 22 , 24 ). Strikingly, in vitro mass-spectrometric analysis of Drosophila C3PO revealed a mixture of ratios of 2:6 and 3:5 (TRAX:Translin) in C3PO, which was partially supported by the reported N. equitans C3PO ( Ne- C3PO) structure ( 21 , 23 ).…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, negative-stained EM structure of full-length Drosophila C3PO at ∼15 Å resolution and cryo-EM structure of human-C3PO at ∼15 Å resolution were also reported ( 23 ). Notably, all the full-length C3POs adopt closed football-shaped structures, which are very similar to previous reported Translin homo-octamer structures ( 8 , 21 , 22 , 24 ). Strikingly, in vitro mass-spectrometric analysis of Drosophila C3PO revealed a mixture of ratios of 2:6 and 3:5 (TRAX:Translin) in C3PO, which was partially supported by the reported N. equitans C3PO ( Ne- C3PO) structure ( 21 , 23 ).…”
Section: Introductionsupporting
confidence: 89%
“…Notably, all the full-length C3POs adopt closed football-shaped structures, which are very similar to previous reported Translin homo-octamer structures ( 8 , 21 , 22 , 24 ). Strikingly, in vitro mass-spectrometric analysis of Drosophila C3PO revealed a mixture of ratios of 2:6 and 3:5 (TRAX:Translin) in C3PO, which was partially supported by the reported N. equitans C3PO ( Ne- C3PO) structure ( 21 , 23 ). In addition, human-C3PO structures showed that the two catalytic TRAX subunits were packed side-by-side in a head-to-tail mode, with the active residues facing into the concaved interior cavity ( 21 ).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, three candidates are related to the microRNA (miRNA) gene-silencing machinery. Specifically, we found that Cnot4, a member of the Ccr4-Not complex that associates with RISC (Collart and Panasenko, 2012), the trinucleotide repeat containing 6a (Tnrc6a, also called GW182), a binding partner of Argonaute (Pfaff et al, 2013), and the trans-lin-associated factor X (Tsnax), which facilitates miRNA loading on RISC (Zhang et al, 2016), were enriched in the NAc polysomal fraction of alcohol-drinking mice but not in alcohol-consuming mice pre-treated with rapamycin. As mTORC1 has recently been shown to play a role in the regulation of miRNA production (Jewell et al, 2015), it would be of interest to assess the consequences of the increased translation of these targets by alcohol.…”
Section: Discussionmentioning
confidence: 99%